Physical activity in elderly - Jan Cvecka; Veronika Tirpakova; Milan Sedliak; Helmut Kern; Winfried Mayr; Dušan Hamar (PAGEPress Publications, 2015)
Aging is a multifactorial irreversible process associated with significant decline in muscle mass and neuromuscular functions. One of the most efficient methods to counteract age-related changes in muscle mass and function is physical exercise. An alternative effective intervention to improve muscle structure and performance is electrical stimulation. In the present work we present the positive effects of physical activity in elderly and a study where the effects of a 8-week period of functional electrical stimulation and strength training with proprioceptive stimulation in elderly are compared.